A Review on the Assessment of Stress Conditions for Simultaneous Production of Microalgal Lipids and Carotenoids - Minhas, Amritpreet K.; Hodgson, Peter; Barrow, Colin J.; Adholeya, Alok (Frontiers in Microbiology, 2016)
Microalgal species are potential resource of both biofuels and high-value metabolites, and their production is growth dependent. Growth parameters can be screened for the selection of novel microalgal species that produce molecules of interest. In this context our review confirms that, autotrophic and heterotrophic organisms have demonstrated a dual potential, namely the ability to produce lipids as well as value-added products (particularly carotenoids) under influence of various physico-chemical stresses on microalgae. Some species of microalgae can synthesize, besides some pigments, very-long-chain polyunsaturated fatty acids (VL-PUFA,>20C) such as docosahexaenoic acid and eicosapentaenoic acid, those have significant applications in food and health. Producing value-added by-products in addition to biofuels, fatty acid methyl esters (FAME), and lipids has the potential to improve microalgae-based biorefineries by employing either the autotrophic or the heterotrophic mode, which could be an offshoot of biotechnology. The review considers the potential of microalgae to produce a range of products and indicates future directions for developing suitable criteria for choosing novel isolates through bioprospecting large gene pool of microalga obtained from various habitats and climatic conditions.